Zakat Profesi - Yenni Samri Juliati; Abdurrozzaq Ismail (Pusat Riset dan Inovasi Nasional, 2024)
Professional zakat is a type of zakat which is specifically related to income or earnings obtained from certain jobs or professions in the Islamic economy. This is a form of zakat given by individuals who have income from their work or business. Professional zakat is one of the topics of contemporary jurisprudence that is still debated and not yet fully agreed upon by scholars. This research was conducted using a descriptive method with a qualitative approach based on data sources from literature studies and observations. The aim of this research is to provide information related to professional zakat. The research results show that Professional Zakat is calculated based on a certain percentage of an individual's income after meeting basic needs and debts that must be paid. The percentage that must be spent varies between 2.5% to 20% depending on the assets owned